2023
DOI: 10.1038/s41598-023-35908-9
|View full text |Cite
|
Sign up to set email alerts
|

Three genes expressed in relation to lipid metabolism considered as potential biomarkers for the diagnosis and treatment of diabetic peripheral neuropathy

Abstract: Diabetic neuropathy is one of the most common chronic complications and is present in approximately 50% of diabetic patients. A bioinformatic approach was used to analyze candidate genes involved in diabetic distal symmetric polyneuropathy and their potential mechanisms. GSE95849 was downloaded from the Gene Expression Omnibus database for differential analysis, together with the identified diabetic peripheral neuropathy-associated genes and the three major metabolism-associated genes in the CTD database to ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Hyperglycemia is known to induce synaptic dysfunction and disrupt the balance of neurotransmitter secretion ( 47 ). Furthermore, differential gene expression analyses in various diabetic tissues were similar to our findings, with overlapping pathways observed in skeletal muscle ( 48 ), β-cell-enriched tissue ( 49 ), diabetic kidney ( 50 , 51 ), and diabetic peripheral neuropathy ( 52 ).…”
Section: Discussionsupporting
confidence: 87%
“…Hyperglycemia is known to induce synaptic dysfunction and disrupt the balance of neurotransmitter secretion ( 47 ). Furthermore, differential gene expression analyses in various diabetic tissues were similar to our findings, with overlapping pathways observed in skeletal muscle ( 48 ), β-cell-enriched tissue ( 49 ), diabetic kidney ( 50 , 51 ), and diabetic peripheral neuropathy ( 52 ).…”
Section: Discussionsupporting
confidence: 87%
“…The studies by Yang et al, and Li et al, have provided insights into the upregulation of ME1 in the context of diabetes. Elevated ME1 expression was observed in patients with diabetic peripheral neuropathy and T2DM, respectively [ 50 , 51 ]. Additionally, Li et al, reported an increase in ME2 expression in T2D patients [ 51 ].…”
Section: Changes In Expression Of Nadph Producing Enzymes In Diabetes...mentioning
confidence: 99%
“…Furthermore, projections indicate that the prevalence of diabetes is expected to rise to 10.2% (578 million) by the year 2030 and 10.9% (700 million) by 2045. While the prevalence of type 2 diabetes is on the rise globally, it is noteworthy that a significant majority of individuals with diabetes, around 79%, reside in low-and middle-income countries (Yang & Wang, 2023). Furthermore, it is anticipated that the increase in prevalence will be particularly pronounced in low-income countries (Kaiser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…People who have diabetes have a greater risk of morbidity and mortality, in addition to increased costs associated with medical care, as comparison to the general population. According to the International Diabetes Federation (IDF), diabetes was the cause of 4.2 million deaths and at least 10% of global health expenditures in 2019 (USD 760 billion dollars) (Yang & Wang, 2023). Diabetes is commonly regarded as a controllable condition through the use of lifestyle adjustments and medical interventions.…”
Section: Introductionmentioning
confidence: 99%